EFFECTIVE LEADERSHIP STYLE TO IMPROVE PERFORMANCE: CASE IN THE TECHNOLOGY SECTOR IN THE ERA OF SOCIETY 5.0 - Riyanto, Fery; Chasanah, Amalia Nur; Puspitasari, Diana; Kadarningsih, Ana; Ibrahim, Nor Fauziana (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2024)
The era of society 5.0 is accompanied by rapid social and economic transformation in all sectors of human life. The demand for rapid change is undoubtedly felt by all sectors, especially technology sector organizations, where they must adapt to change. Leadership has become an important role in this sector because of the demands of change to determine organizational success. Therefore, this research aims to explore effective leadership styles to improve the performance of technology sector employees. The research object and population are employees of the technology sector in Indonesia. This research sample of 249 was obtained from a purposive sampling technique. The research method uses a quantitative approach with Partial Least Square (PLS) with Smart-pls 0.3 software. The research results show that the digital leadership style impacts employee performance; 2) the visionary leadership style impacts employee performance; 3) the servant leadership style impacts employee performance; and 4) the agile leadership style does not impact employee performance.